Multimodal physical therapy intervention based on a biobehavioral approach in a patient with chronic upper limb pain: a case report - Fernando-Balbino Blanco-Fernández; Carlos Forner-Álvarez; Celia Vidal-Quevedo; Ferran Cuenca-Martínez; Mónica Grande-Alonso (Exploration of Neuroprotective Therapy)
Chronic upper limb pain is rather common among people in general and is characterized by a complex diagnosis due to the wide variety of factors that are involved in its development. In terms of treatment, pharmacology and manual therapy have classically been the most used options. However, based on current evidence, recommendations are more inclined to apply multimodal treatments, mainly with exercise therapy and pain education, based on the patient-centered care model. This case report details the evaluation and treatment of a 23-year-old woman with chronic upper limb pain using a multimodal physical therapy with a biobehavioral approach. The intervention lasted 12 weeks with a total of 9 sessions, in which manual therapy, therapeutic exercise, pain neuroscience education, motion representation methods, and sensory retraining were applied. The treatment resulted in a substantial improvement in the patient’s health condition. This case report indicates that a multimodal physical therapy treatment based on a biobehavioral approach may offer benefits in reducing pain symptoms and enhancing somatosensory, motor-functional, and affective-cognitive abilities in patients with chronic upper limb pain, as observed in the described case. Accordingly, this treatment can be a therapeutic option for patients with chronic upper limb pain.